SP6.1.6 Rule of systematic intraoperative cholangiogram in patients undergoing emergency cholecystectomy. (28th October 2021) - Hatem, Fady; Mostafa, Sam; Thomas, Jenny; Nassar, Ahmad
Abstract: Aims: Incidence of gall stone disease is estimated at 10-15%of population. Intraoperative cholangiography (IOC) diagnose choledocholithiasis, delineates the anatomy of the biliary ducts, facilitate the dissection and reduces injuries. Our aim is to assess the feasibility and role of IOC and the incidence of choledocholithiasis in acute cholecystitis (ACC). Methods: Retrospective analysis of prospectively collected data for patients admitted with ACC and undergoing same-hospital-stay laparoscopic cholecystectomy (LC). IOC was systematically attempted in all cases. Results: 475cases included. Female to male ratio1.9:1. Conversion to open was done in 3 cases. Preoperative cholelithiasis was confirmed in 439cases versus 34cases with no stones. USS CBD abnormality (dilated or contain stone) found in 53 cases, out of which 8(15%) cases had CBD stones. Jaundice was found in 69cases, where 25(39%) cases had confirmed choledocholithiasis. IOC was successful in all cases except one. Abnormal IOC was found in 99(21%) cases. Of those; CBD stones were confirmed in 76 (77%) cases regardless the presence of cholelithisasis on USS. Empyema was found in 237 cases and it was associated with higher risk of abnormal IOC in 59(25%) cases where CBD stones were confirmed in 45(76%) cases. Cystic duct (CD) stones found in 80cases, of those 27(34%)cases had choledocholithiasis. Conclusions: Females have double the risk of ACC. Preoperative jaundice and CD stones are stronger indicators than CBD diameter for presence of choledocholithiasis. The incidence of choledocholithiasis in ACC is (20-25%) regardless the presence of gall stones on USS. IOC is feasible and highly recommended in emergency LC.